Serum Endocan Levels Associated with Hypertension and Loss of Renal Function in Pediatric Patients after Two Years from Renal Transplant - Livia Victorino de Souza; Vanessa Oliveira; Aline Oliveira Laurindo; DelmaRegına Gomes Huarachı; Paulo Cesar Koch Nogueira; Luciana de Santis Feltran; José Osmar Medina-Pestana; Maria do Carmo Franco (International Journal of Nephrology)
Endocan is an important biomarker of inflammation and endothelial dysfunction that increases in association with several chronic diseases. Few published data have described the role of endocan in pediatric renal transplant (RT) patients. We evaluated the endocan concentrations in 62 children who underwent renal transplantation and assessed their relationships with the patients’ blood pressure and loss of renal function. The endocan levels were significantly elevated in the pediatric RT patients who had hypertension and a loss of renal function. We determined positive correlations between the endocan concentrations and the hemodynamic variables (systolic blood pressure: r=0.416; P=0.001; pulse pressure: r=0.412; P=0.003). The endocan levels were inversely correlated with the estimated glomerular filtration rate (r=-0.388; P=0.003). An endocan cutoff concentration of 7.0 ng/mL identified pediatric RT patients who had hypertension and a loss of renal function with 100% sensitivity and 75% specificity. In conclusion, the endocan concentrations were significantly elevated in pediatric RT patients who had both hypertension and a loss of renal function. The correlations between the endocan levels and the hemodynamic variables and the markers of renal function strengthen the hypothesis that it is an important marker of cardiorenal risk.